2008
DOI: 10.3141/2073-11
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Pedestrian Signals at Complex Intersections

Abstract: Pedestrians with vision impairments often have to cross streets at unfamiliar signalized intersections. The results are reported of research on crossings by blind pedestrians at complex intersections before and after the installation of accessible pedestrian signals (APS) and again following the installation of innovative device features. Objective data on measures of street crossing performance by 56 participants were obtained at four intersections, two each in Charlotte, North Carolina, and Portland, Oregon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Without it, participants were well aligned on approxi mately half of their trials, while with the guidance surface present and used for alignment, they were on average well aligned on more than threefourths of their individual trials. When pedestrians who are visually impaired are not well aligned when they begin crossing a street, they are quite likely to be outside the crosswalk by the time they reach the opposite end (1,9,10). This misalignment sometimes results in encountering landscaping or some kind of barrier on an island that prevents them from getting out of the street promptly, thus leading to greater exposure to moving traffic, or entirely missing a splitter island at a roundabout or channelized turn lane and walking into traffic lanes on either side of the island (1).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without it, participants were well aligned on approxi mately half of their trials, while with the guidance surface present and used for alignment, they were on average well aligned on more than threefourths of their individual trials. When pedestrians who are visually impaired are not well aligned when they begin crossing a street, they are quite likely to be outside the crosswalk by the time they reach the opposite end (1,9,10). This misalignment sometimes results in encountering landscaping or some kind of barrier on an island that prevents them from getting out of the street promptly, thus leading to greater exposure to moving traffic, or entirely missing a splitter island at a roundabout or channelized turn lane and walking into traffic lanes on either side of the island (1).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Participants typically used either or both the location of the curb ramp and the detectable warning, which were always approximately in the center of the crosswalk width, or the guidance surface, which was beside the detectable warning, also within the width of the crosswalk. In locations having poorly located curb ramps, or lacking detectable warnings, or having curb ramps or blended curbs that are much wider than the crosswalk, aligning to cross from a location within the crosswalk width has been found to be more of a problem (9).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Their findings suggest that under geometrically ideal conditions, traffic sounds can be used to align to within about 10 degrees of the desired direction. At complex intersections without special alignment cues, blind pedestrians have been found to be misaligned prior to crossing between 24% and 50% of the time (Barlow, Bentzen, & Bond, 2005; Scott, Barlow, Bentzen, Bond, & Gubbe, 2008; Crandall, Brabyn, Bentzen, & Myers, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have shown a significant improvement in safety of vision impaired persons at the pedestrian crosswalks after introduction of audible pedestrian traffic signals [1,2]. The study carried out in California in 1991 [1] has shown that after installation of acoustic signalling devices generating audible traffic signals at the pedestrian crosswalks, the number of accidents involving vision impaired persons was reduced.…”
Section: Introductionmentioning
confidence: 99%